2023
DOI: 10.1073/pnas.2315171120
|View full text |Cite
|
Sign up to set email alerts
|

Localization of PPM1H phosphatase tunes Parkinson’s disease-linked LRRK2 kinase-mediated Rab GTPase phosphorylation and ciliogenesis

Wondwossen M. Yeshaw,
Ayan Adhikari,
Claire Y. Chiang
et al.

Abstract: PPM1H phosphatase reverses Parkinson’s disease-associated, Leucine Rich Repeat Kinase 2-mediated Rab GTPase phosphorylation. We show here that PPM1H relies on an N-terminal amphipathic helix for Golgi localization. The amphipathic helix enables PPM1H to bind to liposomes in vitro, and small, highly curved liposomes stimulate PPM1H activity. We artificially anchored PPM1H to the Golgi, mitochondria, or mother centriole. Our data show that regulation of Rab10 GTPase phosphorylation requires PPM1H access to Rab10… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Recent work indicates that the subcellular colocalization of PPM1H with specific RABs strongly influences levels of RAB phosphorylation (Yeshaw et al, 2023). Regulation of RABmediated pathways in neurons is therefore determined by the balance of LRRK2 and PPM1H activities at each specific membrane compartment, in ways that are difficult to predict from whole-cell pRAB levels alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work indicates that the subcellular colocalization of PPM1H with specific RABs strongly influences levels of RAB phosphorylation (Yeshaw et al, 2023). Regulation of RABmediated pathways in neurons is therefore determined by the balance of LRRK2 and PPM1H activities at each specific membrane compartment, in ways that are difficult to predict from whole-cell pRAB levels alone.…”
Section: Discussionmentioning
confidence: 99%
“…S2 F). Notably, PPM1H has been shown to strongly localize to the Golgi (Berndsen et al, 2019;Yeshaw et al, 2023), suggesting that its loss may cause more striking effects on protein sorting and cargo loading at the TGN. Further work could reveal how relative LRRK2-PPM1H abundance at specific subcellular membrane compartments differentially regulates other RAB-mediated pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the PPM1H response to mitochondrial depolarisation was independent of PINK1 and LRRK2 catalytic activity. Over-expression studies have previously revealed that PPM1H is localised mainly to the Golgi complex with further pools of PPM1H associated with the mother centriole and mitochondria although PPM1H does not act on mitochondrial Ser111-phosphorylated Rab8 [16,17]. At the Golgi, PPM1H strongly colocalises with Rab8A, Rab10 and Rab29 but less well with Rab12 and over-expression of PPM1H efficiently dephosphorylates Rab10 but not Rab12 suggesting that its major role is to protects Golgi-associated Rabs from LRRK2 phosphorylation and inactivation [17].…”
Section: Discussionmentioning
confidence: 99%
“…PPM1H is predominantly localised at the Golgi with a small pool located at the mitochondria [16,17]. Moreover, our prior analysis demonstrated that artificial localization of PPM1H to mitochondria blocks its ability to act on Thr72-phosphorylated Rab10 [17]. We next determined whether PPM1H is being targeted to mitochondria following O/A treatment.…”
Section: Ppm1h Is Up-regulated and Recruited To Damaged Mitochondriamentioning
confidence: 98%
See 1 more Smart Citation